Uma breve abordagem histórica da classe dos adjetivos (A brief historical approach of the class of adjectives) - Carvalho, Roberto Santos de; Kanthack, Gessilene Silveira (Estudos da Língua(gem), 2011)
Este artigo apresenta uma parte da história dos estudos dos adjetivos, ao longo do pensamento ocidental, partindo das reflexões gregas, passando pelas bases romanas e suas ramificações. Descreve o contexto do pensamento filosófico em que os adjetivos foram descritos por Platão e demonstra que, em razão do seu comportamento sintático-semântico bastante peculiar, ocorreram tentativas de agrupá-los em distintas classes, visando melhor conhecer o seu comportamento. O objetivo precípuo do artigo é, pois, apresentar um breve panorama histórico da configuração dos adjetivos, com vistas a demonstrar que o interesse por eles tem longa tradição na investigação linguística ocidental. PALAVRAS-CHAVE: Adjetivo. História. Semântica. Sintaxe. ABSTRACT This paper presents an historical overview of adjective study along the western tradition, from the Greek reflections to the Roman roots and their branches. We will describe the context of the philosophical thought in which the adjective categories were described by Plato. Besides, we will demonstrate that, due to the syntactic-semantic behaviour of this grammatical class, many attempts were made in order to group the adjectives in different classes, by aiming at knowing better the fluid behaviour of this category. The main goal of this article is, therefore, to present a general and historical overview of the configuration of the adjective category, and to show that the interest for this grammatical topic follows a long tradition in the western linguistics investigation. KEYWORDS: Adjective. History. Semantics. Syntax.